2002
DOI: 10.1111/1468-2478.00224
|View full text |Cite
|
Sign up to set email alerts
|

Trade Structure and the Effectiveness of America's "Aggressively Unilateral" Trade Policy

Abstract: When does America’s “aggressively unilateral” trade policy work best to open overseas markets? This paper revisits the determinants and effectiveness of Section 301 of U.S. trade law and develops a modified two‐level game model for understanding the conditions under which domestic interests and institutions support the use of aggressive negotiation tactics. It argues that a system‐level variable, the structure of trade, systematically affects threat effectiveness by influencing both the level of unity among do… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…The party affiliation of the U.S. President in office could have a significant effect on American resolve in prosecuting Section 301 cases, as the USTR would be influenced by the president's political prerogatives (e.g., Drury, ). For example, Zeng (, p. 110) found that President Ronald Reagan's 1985 Trade Policy Action Plan (TPAP) had a positive effect on the success of the United States' Section 301 disputes. In launching the TPAP initiative, Schoch (, p. 104) asserts that President Reagan sought both to “shield” Congressional Republicans from partisan attacks on the trade issue and put the issue firmly under Republican control.…”
Section: Empirical Analysismentioning
confidence: 99%
“…The party affiliation of the U.S. President in office could have a significant effect on American resolve in prosecuting Section 301 cases, as the USTR would be influenced by the president's political prerogatives (e.g., Drury, ). For example, Zeng (, p. 110) found that President Ronald Reagan's 1985 Trade Policy Action Plan (TPAP) had a positive effect on the success of the United States' Section 301 disputes. In launching the TPAP initiative, Schoch (, p. 104) asserts that President Reagan sought both to “shield” Congressional Republicans from partisan attacks on the trade issue and put the issue firmly under Republican control.…”
Section: Empirical Analysismentioning
confidence: 99%
“…We do not know if the Special 301 process represents a credible threat, for example. Depending on the targeted countries' export profile, trade sanctions imposed by the U.S. may hurt American importers and therefore may face strong opposition in Washington (Zeng, 2002). 25 Or perhaps countries simply pay little attention to the Special 301 reports, especially when they are listed only on the WL, because they regard them as idle threats with uncertain consequences.…”
Section: Explaining Ipp: National and Transnational Determinantsmentioning
confidence: 99%
“…But the use of these dichotomous classifications had no meaningful effect on our results. We also examined whether the effects of bilateral pressure might be conditional upon the structure of trade relations with the United States (Zeng, 2002), interacting Special 301 and out‐of‐cycle reviews with trade dependence. But, here again, neither of these measures predicted the level of IPP that was delivered, either directly or in interaction with trade dependence.…”
Section: The Evidencementioning
confidence: 99%
“…The central question is whether the political balance shifts sufficiently for policy change to occur, which has prompted some analyses to consider explicitly the impact of domestic decision rules (Dai 2006;Moravcsik 1993;Odell 1993;Zeng 2002). …”
Section: Making Concessions In Response To Mobilized Interestsmentioning
confidence: 99%